2020
DOI: 10.1128/mbio.02293-19
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Use Efficiency and Its Temperature Sensitivity Covary in Soil Bacteria

Abstract: The strategy that microbial decomposers take with respect to using substrate for growth versus maintenance is one essential biological determinant of the propensity of carbon to remain in soil. To quantify the environmental sensitivity of this key physiological trade-off, we characterized the carbon use efficiency (CUE) of 23 soil bacterial isolates across seven phyla at three temperatures and with up to four substrates. Temperature altered CUE in both an isolate-specific manner and a substrate-specific manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(49 citation statements)
references
References 89 publications
6
43
0
Order By: Relevance
“…Furthermore, Pold et al 13 show that the Q 10 of CUE is higher for more efficient taxa which is analogous to our result of a negative relationship between E CUE and maximum CUE. We find that this trade-off is well described as a linear relationship, with highly negative E CUE values not being found, suggesting a potential biological limit.…”
Section: And S2supporting
confidence: 91%
“…Furthermore, Pold et al 13 show that the Q 10 of CUE is higher for more efficient taxa which is analogous to our result of a negative relationship between E CUE and maximum CUE. We find that this trade-off is well described as a linear relationship, with highly negative E CUE values not being found, suggesting a potential biological limit.…”
Section: And S2supporting
confidence: 91%
“…This was confirmed by a break point analysis which showed a threshold at a PD value of 4.48 after which only high CUE values were observed ( t = 4.51, df = 86, R 2 = 0.28, P < 0.001). By contrast, the lower diversity samples showed the full range of CUE values suggesting that other factors such as community composition 22 and environmental factors are important in determining community CUE. While we report a positive relationship between diversity and CUE, other studies have evaluated the relationship between respiration and diversity, and found it to be positive 8 , 44 , neutral 44 , 45 , or negative 46 .…”
Section: Resultsmentioning
confidence: 85%
“…This decrease in CUE for communities incubated at higher temperature was associated with an increase in estimated rrN copy number (Supplementary Fig. 12 ), a high rrN copy number has been related to a lower growth efficiency 53 , although this has not always been observed 22 . Moisture treatment showed no significant impact on either CUE ( t = −1.81, df = 161, P = 0.070) or rrN (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations